KEROSENE TANK DESIGN WITH 30.000 M3 AS ITS REQUIRED CAPACITY BASED ON API STANDARD 650 AND VERIFIED WITH FINITE ELEMENT METHODE - BASUKI (NIM : 13104002); Pembimbing : Dr. Ir. Rachman Setiawan, YANUAR
The tank is mechanical equipment useful for storing liquid fluids such as crude oil, liquid chemicals, or water. For the tank with a relatively large diameter, in addition to using standard, design elements also use this method until the tank to ensure the strength of the various loads. This final project explain about kerosene tank design with 30.00 m3 as its required capacity and verified by finite element method. Element analysis is including analysis of the strength of the tank due to hydrostatic pressure load, wind, and earthquake, with the help of Ansys software version 11. The result of this final project is tank design with a diameter of 49.57 m and height of 18.275 m. Thick bottom course of 26 mm to 8 mm of the top 8 course. From the analysis of elements up to, the maximum stress occurs in a total of 178 MPa, for the most extreme cases, the result of the earthquake load with SF = 1.4. While the maximum deflection of 29.1 mm occurred on the 4th ring girder, lower than the limit of the maximum deflection of 91.4 mm. From the above it can be concluded that the design of the tank in this final project is considered safe.